2021
DOI: 10.1007/s42235-021-00116-6
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Aerodynamic Performance of Wingtip Slots and Research Prospect

Abstract: Wingtip slots, where the outer primary feathers of birds split and spread vertically, are regarded as an evolved favorable feature that could effectively improve their aerodynamic performance. They have inspired many to perform experiments and simulations as well as to relate their results to aircraft design. This paper aims to provide guidance for the research on the aerodynamic mechanism of wingtip slots. Following a review of previous wingtip slot research, four imperfections are put forward: vacancies in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 125 publications
1
5
0
Order By: Relevance
“…Te fences direct the vortices formed on the wing to the rear and towards the trailing edge and cause the outer parts of the wing not to have problems in producing drag [16]. Te studies presented in (9)(10)(11)(12)(13)(14)(15)(16) align with the present investigation in their exploration of vortex phenomena on aircraft wings and the potential for vortex control devices.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Te fences direct the vortices formed on the wing to the rear and towards the trailing edge and cause the outer parts of the wing not to have problems in producing drag [16]. Te studies presented in (9)(10)(11)(12)(13)(14)(15)(16) align with the present investigation in their exploration of vortex phenomena on aircraft wings and the potential for vortex control devices.…”
Section: Introductionsupporting
confidence: 69%
“…In addition to the above, this tool plays a role in improving the performance of the wing and controls surfaces and changes in the wing tip vortices [11]. A practical and more efective way to deal with vortices is wing fences, which have been seen in nature and some birds [12]. Wing fences were invented by Wolfgang Liebe in 1938 to delay the excessive movement of the eddy current along the wing and its rapid increase [13].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [74] reviewed previous studies of birds' slotted wingtips and proposed some interesting insights into wingtip vortices. The authors cited a study conducted by Tuker on Harris hawks with clipped and unclipped (slotted) wingtips flying freely inside a wind tunnel.…”
Section: Slo Ed/serrated Wingtipmentioning
confidence: 99%
“…showed that, compared to the solid winglet, slo ed winglets typically have a 7.6-14% higher lift coefficient with a penalty of 8-14% induced drag. Liu et al [74] reviewed previous studies of birds' slo ed wingtips and proposed some interesting insights into wingtip vortices. The authors cited a study conducted by Tuker on Harris hawks with clipped and unclipped (slo ed) wingtips flying freely inside a wind tunnel.…”
Section: Slo Ed/serrated Wingtipmentioning
confidence: 99%
“…1 Introduction Among animals capable of flight, the wings of birds stand out by being built from multiple, partly overlapping, individual structures -feathers. The fact that feathers are individual structures allows the outermost primary flight feathers in many birds to separate and function as aerofoils on their own (KleinHeerenbrink et al, 2017), as seen in the multi-slotted wingtips (Figure 1) of, for example, birds of prey (Liu et al, 2021). The morphology of these latter feathers shows distinct properties, such as a smaller chord in the part that work as an independent aerofoil than in the part where feathers overlap as well as a high asymmetry in the location of the shaft along the chord (Feo et al, 2015).…”
mentioning
confidence: 99%